"How do you prove a negative?" : Roger Clemens's image-repair strategies in response to the Mitchell report - Sanderson, Jimmy (London : Human Kinetics, Inc., 2008)
This case study examines star Major League Baseball pitcher Roger Clemens's image-repair strategies during a press conference he held to respond to allegations that he had used steroids and human-growth hormones earlier in his playing career. When professional athletes are confronted with allegations of cheating or illegitimately enhancing their athletic performance, they are faced with a crisis situation, and selecting and performing the appropriate response is paramount in repairing their image and mitigating personal harm (e.g., loss of endorsements). In many cases, however, professional athletes rely on attorneys, agents, or other individuals who might underestimate the relevance of appropriately communicating image repair, thereby resulting in the athlete's image being further damaged. Although Clemens employed various image-repair strategies during his press conference, his failure to enact these strategies appropriately further harmed his reputation and ultimately raised more questions than he answered.
Originally published in Sanderson, J. (2008). "How do you prove a negative?": Roger Clemens's image-repair strategies in response to the Mitchell Report. International Journal of Sport Communication, 1(2), 246-262. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Clemens, Roger; Baseball players -- United States -- Biography; Athletes -- Drug use -- United States; Steroid abuse -- United States; Doping in sports -- History